PEMANFAATAN MEDIA INTERNET OLEH PENYULUH DALAM UPAYA PERCEPATAN DISEMINASI INFORMASI PERTANIAN / The Utilization of Internet By Extension Specialist in Efforts to Accelerate Agriculture Information Disemination - Eni Kustanti; Agus Rusmana; Purwanti Hadisiwi (Badan Penelitian dan Pengembangan Pertanian, 2020)
One of the internet utilization inagricultural developmentby the Ministry Agriculture is to disseminate information of technology innovations to the agricultural extension specialist as intermediary users. This paper discusses the use of the internet by agricultural extension specialist in an effort to accelerate the dissemination of agricultural information. Several internet application used in the dissemination of agricultural information such as the IAARD(Indonesia Agency of Agricultural Research dan Development) website, cyber extension, agricultural digital libraries and social media.The intensity of using the internet by agricultural extension specialist for dissemination of agricultural informastion is still low with the frequency of 2-3 times a day and the duration of 1-2 hours a day because the task of agricultural extension in the field. The used of the internet by agricultural extension are depend on individual characteristic (age, length of work, media ownershipand education), perception on the internet, information needs, motivation and support of agencies. The agricultural extension used the internet for reports, content creation, and extension methods designed. Low internet acces capability and limited access facilities become obstacles on using the internet to obtain the necessary information. The ability of extension specialist to access the internet can meet the needs of agricultural information users and improve the competence of extension specialist themselves.Keyword: Internet, dissemination, agricultural technology, extension. AbstrakSalah satu pemanfaatan internet di Kementerian Pertanian adalah untuk diseminasi informasi teknologi pertanian kepada penyuluh sebagai pengguna perantara sebelum disampaikan ke petani dengan bahasa yang mudah dicerna. Tulisan ini membahas pemanfaatan internet oleh penyuluh dalam upaya percepatan diseminasi informasi pertanian. Beberapa aplikasi internet untuk diseminasi informasi pertanian diantaranya web Balitbangtan, cyber extension, perpustakaan digital pertanian, dan media sosial. Intensitas penggunaan internet oleh penyuluh untuk diseminasi informasi pertanian masih rendah dengan frekuensi 2-3 kali sehari dan durasi 1-2 jam sehari karena mereka lebih banyak berada di lapangan untuk tugas penyuluhan kepada petani. Penggunaan internet oleh penyuluh antara lain dipengaruhi oleh karakteristik individu (usia, lama bekerja, kepemilikan media, dan pendidikan), persepsi terhadap internet, kebutuhan informasi, motivasi dan dukungan lingkungan. Bagi penyuluh, internet digunakan untuk penyusunan laporan, pembuatan materi, program, dan mendesain metode penyuluhan. Kemampuan akses yang rendah dan keterbatasan sarana parasarana menjadi hambatan dalam pemanfaatan internet untuk memperoleh informasi yang diperlukan. Kemampuan penyuluh mengakses internet berperan penting dalam memenuhi kebutuhan pengguna informasi pertanian dan meningkatkan kompetensi penyuluh itu sendiri.Kata kunci: Internet, diseminasi, teknologi pertanian, penyuluh.